Climate Variability and Health: Sweden 1751-2004 - Niclas A. Krüger (Örebro University School of Business, 2008)
Several studies have examined the link between climate and health, mainly focusing on the short term impacts of extreme temperatures. This paper analyzes instead the long term relation between climate variability and health using Swedish temperature and mortality data for the period 1751-2004 using different time scales. We find that periods with higher temperature are associated with lower mortality. The results indicate that long term climate variations in annual mean temperatures and not short term variations explain the connection between temperature and mortality. Considering annual extreme temperatures, we find that extreme low winter temperatures are correlated with higher short term mortality. We identify the impact of the 11-year solar cycle on crop yields as a possible explanation for our findings. The results have besides their economic-historical merits implications for modern day policy for developing countries, especially since the correlation with solar activity implies predictability.
Keywords: I18; N53; N54; Q54; 330; Mortality; Wavelet; Climate